2007
DOI: 10.1007/s10267-006-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and developmental factors influencing aflatoxin production by Aspergillus flavus and Aspergillus parasiticus

Abstract: Afl atoxins are carcinogenic mycotoxins formed by a number of fungi in the genus Aspergillus. The major fungi responsible for afl atoxin formation in crop seeds in the fi eld and in storage are Aspergillus fl avus and A. parasiticus. This review emphasizes developmental, environmental, biological, and chemical factors that infl uence afl atoxin formation by A. fl avus and A. parasiticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 127 publications
5
96
1
11
Order By: Relevance
“…The presence of both Aspergillus species in the same grain is very common (Figure 2). Previous studies had shown that A. niger frequently co-occurred with A. flavus in the field (Klich, 2007). Hill et al (1983) had noticed that when the ratio of grain colonised by A. flavus compared with A. niger was >19:1, there aflatoxin contamination occurred, but there was no contamination with this mycotoxin if the ratio was <9:1.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both Aspergillus species in the same grain is very common (Figure 2). Previous studies had shown that A. niger frequently co-occurred with A. flavus in the field (Klich, 2007). Hill et al (1983) had noticed that when the ratio of grain colonised by A. flavus compared with A. niger was >19:1, there aflatoxin contamination occurred, but there was no contamination with this mycotoxin if the ratio was <9:1.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus is a large genus composed of more than 180 accepted anamorphic species (Pitt et al, 2000), with teleomorphs described in nine different genera (Pitt et al, 2000). The genus is subdivided in 7 subgenera, which in turn are further divided into sections (Klich, 2007).…”
Section: Groundnut Contaminated With the Moldmentioning
confidence: 99%
“…Uma das micotoxinas de maior significado em saúde pública e na agricultura são as aflatoxinas, produzidas com maior frequência pelas espécies Aspergillus flavus e A. parasiticus. Estas toxinas são extremamente carcinogênicas e teratogênicas (Klich, 2007).…”
Section: Introductionunclassified